Melatonin as a preventive and curative therapy against pulmonary hypertension. Issue 3 (11th August 2015) - Maarman, Gerald; Blackhurst, Dee; Thienemann, Friedrich; Blauwet, Lori; Butrous, Ghazwan; Davies, Neil; Sliwa, Karen; Lecour, Sandrine
Abstract Pulmonary hypertension (PH) is characterized by elevated pulmonary arterial pressure, which leads to right ventricular (RV) hypertrophy and failure. The pathophysiological mechanisms of PH remain unclear but oxidative stress is believed to contribute to RV dysfunction. Melatonin is a powerful antioxidant and is cardioprotective against ischemia–reperfusion injury and hypertension. Therefore, we hypothesized that a chronic treatment with melatonin, given as a curative or preventive therapy, may confer cardiovascular benefits in PH. PH was induced in Long Evans rats (n ≥ 6 per group), with a single subcutaneous injection of monocrotaline (MCT, 80 mg/kg). Melatonin was given daily in the drinking water, with the treatment starting either on the day of the injection of MCT (dose testing: melatonin 75 ng/L and 6 mg/kg), 14 days after the injection of MCT (curative treatment: 6 mg/kg), or 5 days before the injection (preventive treatment: 6 mg/kg). The development of PH was assessed by measuring RV hypertrophy, RV function, cardiac interstitial fibrosis, and plasma oxidative stress. Compared with controls, MCT‐treated rats displayed RV hypertrophy and dysfunction, increased interstitial fibrosis, and elevated plasma oxidative stress. A chronic melatonin treatment (75 ng/L or 6 mg/kg) reduced RV hypertrophy, improved RV function and reduced plasma oxidative stress. Curative and preventive treatment improved RV functional and plasma oxidative stress parameters and reduced cardiac interstitial fibrosis. Our data demonstrate that melatonin confers cardioprotection in this model of PH. As melatonin is an inexpensive and safe drug, we propose that clinical investigation of the effects of melatonin on RV function in patients with PH should be considered.